Memória, significações locais e míticas na produção artística de Calasans Neto - Carvalho, Maria do Perpétuo Socorro M. Freire de (2013)
The main objective of this research is to portray the work of Calasans Neto, relating his memories to the sociocultural context of Bahia, as well as with local and mythical meanings represented symbolically by goats and whales, which are present in the life of this artist. The methodological basis is based on studies made by the authors Arjun Appadurai (2004) and Yuri Lotman (1996), covering topics such as symbolic universe, imagination and memory. The bibliographic survey of the author Myriam Fraga and theoretical bases of Jerusa Pires Ferreira on Semiotics of Culture, Myths, Culture, Imagination and Orality will have great relevance. This exploratory (Gil, 2010) and field research, sometimes fulfilling an ethnographic role, aims to provide greater familiarity with the life and work of this printmaker of Bahia. Support is in document analysis, bibliographic research and in interviews. Data collection involves a bibliographic survey and interviews with people who knew Calasans Neto, in order to draw a profile of the artist, contextualizing him as printmaker and realizing the influences in his artistic production, received from other artists and his participation as a member of Map Generation (movement of young artists who revolutionized the culture of Bahia). The corpus analysis and interviews will be part of the artist's work, related mainly to two symbolic elements: goats and whales. Some pictures and images of works of art that bring cultural and mythological references of Bahia will be considered sources of complementary research